2013
DOI: 10.1186/1755-7682-6-47
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of quetiapine versus haloperidol in first-episode schizophrenia: a randomized clinical trial

Abstract: BackgroundSchizophrenia is a chronic disease of global importance. The second-generation antipsychotic quetiapine has a favorable side-effect profile, however, its clinical effectiveness has been called into question when compared with first-generation antipsychotics such as haloperidol. This study evaluates the efficacy and tolerability of quetiapine versus haloperidol for first-episode schizophrenia in the outpatient setting.Methods156 adult patients with first-episode schizophrenia participated in an outpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…We included a total of 278 RCTs (see flow diagram in the online supplement); one systematic review of 138 trials (N=47,189) ( 17 ) and 24 additional trials (N=6,672) ( 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ) for SGAs versus other SGAs, and one systematic review of 111 trials (N=118,503) ( 45 , 46 ) and five additional trials (N=1,055) ( 35 , 47 , 48 , 49 , 50 ) for FGAs versus SGAs. The two systematic reviews also included 33 cohort studies (N =652,505) ( 17 , 45 , 46 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We included a total of 278 RCTs (see flow diagram in the online supplement); one systematic review of 138 trials (N=47,189) ( 17 ) and 24 additional trials (N=6,672) ( 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ) for SGAs versus other SGAs, and one systematic review of 111 trials (N=118,503) ( 45 , 46 ) and five additional trials (N=1,055) ( 35 , 47 , 48 , 49 , 50 ) for FGAs versus SGAs. The two systematic reviews also included 33 cohort studies (N =652,505) ( 17 , 45 , 46 ).…”
Section: Resultsmentioning
confidence: 99%
“…All‐cause discontinuation of treatment was not reported in the systematic review of FGAs versus SGAs ( 45 ). However, withdrawals due to adverse events were significantly higher with haloperidol use compared with aripi‐prazole (eight RCTs, RR=1.25), olanzapine (24 RCTs, RR=1.89), risperidone (25 RCTs, RR=1.32), and ziprasidone (27 RCTs, RR=1.68) ( 35 , 45 , 47 , 48 , 49 ). There were no differences in withdrawal due to adverse events in comparisons of haloperidol and clozapine (five RCTs) or quetiapine (10 RCTs).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent clinical studies indicated that second generation atypical antipsychotic agents (clozapine, ziprasidone, quetiapine and olanzapine) improve cognitive impairment, whereas typical agents, such as haloperidol, exerted no effect (6,7). The cognitive tests of the atypical antipsychotics in preclinical studies demonstrate normal cognitive functions, which is in contrast to the classical antipsychotics.…”
Section: Introductionmentioning
confidence: 92%
“…It seldom causes EPS and is a prolactin-sparing antipsychotic drug. It causes metabolic and cardiac adverse effects like risperidone [10]. The patient in case report 2 was treated with quetiapine, and the psychotic and affective symptoms were improved very much.…”
Section: Quetiapinementioning
confidence: 99%